Values and the Organization: Suggestions for Research - Connor, Patrick E.; Becker, Boris W. (Academy of Management Journal, 1975)
Despite long interest in human values, few investigators have focused on values and organizational process. Questions regarding how values relate to reward structure, upward mobility, goal commitment, and control are unresolved. An organizational paradigm to identify reciprocal effects of values and organizational factors is presented and hypotheses for research are offered.